Mapping Students’ Misconceptions in Chemical Bonding Using the Four-Tier Diagnostic Test - Muhamad Fadli; Napsin Palisoa (Universitas Negeri Gorontalo, 2026)
Students’ understanding of Lewis structures and the octet rule remains a fundamental challenge in chemistry learning and is frequently characterized by conceptual difficulties. This study aims to describe the conceptual understanding profile of Chemistry Education students on Lewis structures and related sub-concepts using a Four-Tier Diagnostic Test. A descriptive quantitative research design was employed, involving 17 students from the Chemistry Education Study Program. The diagnostic instrument consisted of 15 items representing valence electrons, Lewis structures–octet rule, formal charge, resonance, octet exceptions, central atom determination, and coordinate covalent bonding.The results indicate that students’ conceptual understanding is dominated by non-scientific categories. Only 10.20% of responses demonstrate sound conceptual understanding, whereas misconceptions and lack of knowledge account for 41.57% and 48.24% of responses, respectively. These findings suggest that most students have not yet developed an adequate conceptual understanding of Lewis structures. Item-level analysis reveals pronounced conceptual weaknesses in the Lewis structures–octet rule concept, as well as a complete lack of conceptual knowledge in formal charge, resonance structure determination, odd-electron octet exceptions, and central atom determination. Furthermore, very high proportions of misconceptions (94.12%) are identified in specific diagnostic items related to resonance concepts and coordinate covalent bonding.Overall, the findings demonstrate widespread conceptual difficulties across advanced subtopics related to Lewis structures, highlighting the need for instructional strategies that emphasize conceptual change and strengthen students’ representational understanding.